2015
DOI: 10.7821/naer.2015.7.124
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a Cooperative Learning Program on the Academ-ic Achievement in Mathematics and Language in Fourth Grade Students and its Relation to Cognitive Style

Abstract: This study is expected to determine the impact of a program based on the cooperative learning methodology. This, in comparison to a traditional learning situation in both mathematics and language achievement. The study was carried out on a group of fourth grade students of primary school. In addition, it tried to find the differential impact according to the cognitive style in the field dependence-independence dimension. This work was carried out with 76 students of the Colegio José Martí I.E.D. (Bogotá-Colomb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 15 publications
3
10
0
1
Order By: Relevance
“…Both groups, however, made significant gains; however, indicating the grouping did not have a significant impact on the difference in posttest scores for the two groups. This finding supports the majority of research on cooperative learning being a viable teaching strategy (Baer, 2003;Igel & Urquhart, 2012;Smith et al, 2014;Valdez et al, 2015;Vega & Hederich, 2015;Zakaria et al, 2013;Zamani, 2016). This research, however, contradicts the findings from Baer (2003),Van der Smith and Spindle (2007), and Zamani (2016) that all found that grouping techniques did make a significant impact on student achievement.…”
Section: Discussionsupporting
confidence: 62%
“…Both groups, however, made significant gains; however, indicating the grouping did not have a significant impact on the difference in posttest scores for the two groups. This finding supports the majority of research on cooperative learning being a viable teaching strategy (Baer, 2003;Igel & Urquhart, 2012;Smith et al, 2014;Valdez et al, 2015;Vega & Hederich, 2015;Zakaria et al, 2013;Zamani, 2016). This research, however, contradicts the findings from Baer (2003),Van der Smith and Spindle (2007), and Zamani (2016) that all found that grouping techniques did make a significant impact on student achievement.…”
Section: Discussionsupporting
confidence: 62%
“…Field-dependent students displayed the highest gain in mathematics and language achievement tests. More recently, a study employed the same methodology but reported different results [60]. The authors reported that co-operative learning increased post-test results in mathematics, irrespective of whether students had a preference for working independently (field-independent style) or in groups (field-dependent style).…”
Section: Resultsmentioning
confidence: 99%
“…However, in the language domain, co-operative learning was only effective for individuals who identified a preference for working independently (field-independent). In summary, the studies present mixed results on whether the teaching practices should aim to match student’s learning style [58,59,60]. Moreover, because there is a focus on the environment and teaching practices, these studies speak less about how differences are manifested in children’s thinking.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations